"I profess to have made no discovery". James Mill on comparative advantage. Issue 1 (2nd January 2022) - Faccarello, Gilbert
Abstract: During recent decades, David Ricardo's ideas on international trade have been submitted to new scrutiny. This research has led to a new understanding of the so-called 'principle of comparative advantage' and shown that the alleged 'Ricardian' model of foreign trade is based on a misunderstanding of Ricardo's text. The present paper focuses on the role of James Mill in the creation of the Ricardian vulgate. It shows how the evolution of Mill's thought, in part due to a didactic perspective and some difficulties raised by his numerical examples, distorted Ricardo's approach. In Mill we find all the ingredients of what is called the 'Ricardian' model of foreign trade, substituting an ex-ante perspective for Ricardo's ex-post approach.